Internalisasi Nilai Agama Melalui Program Ta'lim Jumat dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam - Andrian Prasetyo; Fina Cahyati; Widya An Nur Rohmi; Eva Ruslindasari; Adistia Rahma Putri; Rivo Arkaan Nur Sayyidina (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
This study investigates the implementation of Friday morning and afternoon ta'lim (religious instruction) programs at SMPN 1 Bandar, Pacitan Regency, driven by the critical need to fortify adolescent moral development against contemporary digital-era challenges. It specifically evaluates how these co-curricular activities reinforce students' learning achievements in Islamic Religious Education (PAI). Operating within a descriptive qualitative field research design, data were compiled through participant observations, semi-structured interviews, and student report-card documentation. Informants were selected via purposive sampling, consisting of the headmaster, PAI instructors, and student representatives. The empirical data were systematically processed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the structured Friday programs successfully expand the conventional classroom paradigm. The morning session delivers universal moral habituation, while the gender-segregated afternoon session optimizes practical jurisprudence (fiqh) and reproductive health literacy. Quantifiably, the program yields a comprehensive enhancement across three educational domains: cognitive progression evidenced by higher PAI report marks, psychomotor mastery shown through fluent Qur'anic recitation and accurate worship mechanics, and affective transformation manifested in heightened discipline and interpersonal courtesy. This study underscores that integrating structured non-formal religious activities into public school ecosystems serves as a highly predictable catalyst for holistic PAI academic achievement, provided that structural limitations such as constrained session duration are continuously moderated by collaborative faculty supervision.